Point-of-care echocardiographic screening for left-sided valve heart disease: high yield and affordable cost in an elderly cohort recruited in primary practice. Issue 3 (September 2019) - Williams, Catrin; Mateescu, Anca; Rees, Emma; Truman, Kirstie; Elliott, Claire; Bahlay, Bohdana; Wallis, Ailsa; Ionescu, Adrian
Abstract : Background: Data about the epidemiology of valvular heart disease (VHD) in the elderly is scarce. Hand-held ultrasound devices (HUDs) enable point-of-care ultrasound scanning (POCUS) but their use in an elderly population has not been reported for VHD screening in primary practice. Methods: One hundred consecutive subjects aged >70 years without a VHD diagnosis had 2D and colour Doppler POCUS by an accredited sonographer, using a contemporary HUD (Vscan), in a primary practice setting. Patients with left-sided valve pathology identified by Vscan were referred for formal echo in the local tertiary cardiac centre. Results: Mean age (s.d. ) was 79.08 (3.74) years (72–92 years); 61 female. By Vscan, we found five patients with ≥moderate aortic stenosis (AS), eight with ≥moderate mitral regurgitation (MR) and none with ≥moderate aortic regurgitation. In the AS and MR groups each, one patient had valve intervention following from the initial diagnosis by Vscan, two and one respectively are under follow-up in the valve clinic, while two and four respectively refused TTE or follow-up. Two patients with moderate MR by Vscan had mild and mild/moderate MR respectively by TTE and were discharged. Total cost for scanning 100 patients was 18, 201 – i.e. 182/patient. Conclusions: Screening with a hand-held scanner (Vscan), we identified 5/100 elderly subjects who needed valve replacement or follow-up in valve clinic, at a cost of 182/patient. These findings have potential significance for the allocation of resources in the context of an ageing population.